Overview on population screening for carriers with germline mutations in mismatch repair (MMR) genes in China - Min Zhang; Tianhui Chen (Hereditary Cancer in Clinical Practice, 2021)
Abstract DNA mismatch repair (MMR) genes play an important role in maintaining genome stability. Germline mutations in MMR genes disrupt the mismatch repair function and cause genome instability. Carriers with MMR germline mutations are more likely to have MMR deficiency and microsatellite instability (MSI) than non-carriers and are prone to develop colorectal cancer (CRC) and extracolorectal malignancies, known as Lynch syndrome (LS). MMR gene testing for suspected mutation carriers is a reliable method to identify the mutation types and to discover mutation carriers. Given that carriers of MMR germline mutations have a higher risk of LS-related cancers (LS-RC) and a younger age at onset than non-carriers, early surveillance and regular screening of relevant organs of carriers are very important for early detection of related cancers. This review mainly focuses on the general status of MMR carriers, the approaches for early detection and screening, and the surveillance of MMR mutation carriers in China. Population screening of MMR germline mutation carriers in China will be helpful for early detection, early diagnosis and treatment of MMR mutation carriers, which may improve the 5-year survival, and reduce mortality and incidence rate in the long term.